The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/oby.21394
|View full text |Cite
|
Sign up to set email alerts
|

Chronic endothelin‐1 infusion causes adipocyte hyperplasia in rats

Abstract: Objective: The aim of this study was to investigate the regulatory mechanism of endothelin-1 (ET-1), an endothelium-derived vasoconstrictor, on adipogenesis in vitro and in vivo. Methods: 3T3-L1 preadipocytes were used to explore the mechanisms mediating ET-1 actions on preadipocyte proliferation and adipocyte differentiation. To investigate the in vivo effect of ET-1, male Sprague-Dawley rats were infused with ET-1 or saline for 4 weeks via intraperitoneally implanted osmotic pumps, and the fat pad weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It also has cytokine-like effects, influences cellular DNA synthesis and positively affects the expression of proto-oncogenes and cell proliferation. Previous findings ( 9 ) have shown that ET synergized with other growth factors to activate proto-oncogenes and promoted cell mitosis and proliferation. Thus, it plays an important role in the pathogenesis and tumor development ( 10 ).…”
Section: Discussionmentioning
confidence: 85%
“…It also has cytokine-like effects, influences cellular DNA synthesis and positively affects the expression of proto-oncogenes and cell proliferation. Previous findings ( 9 ) have shown that ET synergized with other growth factors to activate proto-oncogenes and promoted cell mitosis and proliferation. Thus, it plays an important role in the pathogenesis and tumor development ( 10 ).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, different gene silencing techniques such as siRNA and shRNA, together with different transfection procedures (adenovirus, lentivirus transfection, and plasmid electroporation) have been applied to study the function of different genes associated with adipogenesis in 3T3-L1 cells. In particular, inflammatory pathways, adipokine synthesis, and secretion of study enzyme’s function have been investigated through gene silencing in adipocytes [ 43 , 44 , 45 , 46 , 47 ]. These cells have also been useful for deciphering the biological role of several miRNAs, such as miRNA-195a, which plays an essential role in various cellular processes including proliferation and differentiation [ 48 ].…”
Section: Animal Cell Modelsmentioning
confidence: 99%
“…13,56 In addition, ET-1 increases adipocyte hyperplasia after 4 weeks of infusion. 57 through a putative mechanism that may involve the transcription factor activator protein-1 (AP-1). 60 In cultured neonatal rat cardiomyocytes, leptin was shown to elevate ET-1 and reactive oxygen species (ROS) levels resulting in cellular hypertrophy.…”
Section: Adipose and Et-1mentioning
confidence: 99%
“…This glucose is necessary for the formation of glycerol and the subsequent conversion of free fatty acids into its storage form of triacylglycerol 13,56 . In addition, ET‐1 increases adipocyte hyperplasia after 4 weeks of infusion 57 . Therefore, elevated plasma ET‐1 and states of low insulin or IR both function to increase levels of plasma free fatty acids by increasing adipocyte lipolysis and decreasing the storage of free lipids.…”
Section: Adipose and Et‐1mentioning
confidence: 99%